Frontiers Review: Severe Asthma in Adolescents - Warraich, Sara; Sonnappa, Samatha (Frontiers in Pediatrics, 2022)
Asthma remains the most prevalent chronic respiratory disease of childhood. Severe asthma accounts for a minority group of patients but with substantial morbidity burden. It may reflect disease which is resistant to treatment or that which is difficult to treat, or a combination of both. The adolescent patient cohort denote a unique group and are the focus of this review. This group of patients embody transitioning priorities and evolving health beliefs, all of which may influence the management and burden of disease. Factors of importance include the influence of physiological parameters such as sex and race, which may confer implications for medical management and non-physiological factors, such as adherence, risk-taking behaviour and vaping. The holistic approach to management of severe asthma within this group of patients must acknowledge the evolving patient independence and desire for autonomy and strive for a collaborative, patient tailored approach. This review will focus on the factors that may pose a challenge to the management of severe adolescent asthma whilst offering suggestions into changes in practice that might harness patient priorities and shared clinical decision-making.